Exclusion of chromosomal abnormalities and microdeletions 22q11 and 10p13 in Algerian patients with isolated conotruncal malformation - Ammar-Khodja, F.; Abdellali, M. (Цитология и генетика, 2015)
The chromosomal abnormalities of number and structure or the 22q11.2 and 10p13-14 microdeletions are considered the main causes of congenital heart disease. In our best knowledge, cytogenetics studies on congenital heart diseases (CHD) have not been performed in Algeria. In this study, we will screen for chromosomal abnormalities and microdeletions of 22q11.2 and 10p13 in a cohort of Algerian patients. G-banded by trypsin Giemsa (GTG) and Fluorescent In Situ Hybridization (FISH) techniques have been performed to screen for chromosomal abnormalities and a critical regions 22q11.2 and 10p13-14 respectively in seventy patients with non syndromic congenital heart. GTG technique visualized no chromosomal abnormalities of number and structure in our patients. Moreover, FISH visualizing critical regions 22q11.2 and 10p13-14 respectively did not detect any microdeletion in the chromosomes 10 and 22 respectively of our patients. Our study could suggest that congenital heart defects observed in Algerian patients are not due to chromosomal abnormalities of number and structure nor the 22q11.2 and 10p13-14 microdeletions. For the fist time, we report here cytogenetics analysis of chromosomal abnormalities and the 22q11.2 and 10p13-14 microdeletions in Algerian patients with congenital heart disease. Genetic testing for screening for deletion 22q11.2 and 10p13-14 is not indicated in all patients with isolated conotruncal defects. In addition, conotruncal heart diseases have a multifactorial background like consanguinity and recessive mutations in some genes involved in cardiac morphogenesis. A genetic study to screen for the role of consanguineous marriages and some genes linked to CHD in Algerian population is on going. This study will focus also on health education for the families at risk about the importance of pre-marital genetic counseling. Хромосомные аномалии числа и структуры или микроделеции 22q11.2 и 10p13-14 считаются главными причинами врожденного порока сердца. Насколько нам известно, цитогенетические исследования врожденного порока сердца (CHD) в Алжире не проводились. В настоящей работе проведен скрининг хромосомных аномалий и микроделеций 22q11.2 и 10p13-14 в группе алжирских пациентов. Методы окраски по Гимза (GTG) и FISH были использованы для скрининга хромосомных аномалий и критичных участков 22q11.2 и 10p13-14 соответственно у 70 пациентов с несиндромным врожденным пороком сердца. GTG не выявило хромосомных аномалий по числу и структуре. Более того, изучение участков 22q11.2 и 10p13-14 не показало никаких микроделеций в хромосомах 10 и 22. Наши исследования позволяют сделать вывод, что дефекты, вызванные врожденным пороком сердца у алжирских пациентов, не связаны ни с хромосомными аномалиями числа и структуры, ни с микроделециями 22q11.2 и 10p13-14. Впервые проведен цитогенетический анализ хромосомных аномалий и микроделеций 22q11.2 и 10p13-14 у алжирских пациентов с врожденным пороком сердца. Генетическое тестирование скрининга на наличие делеций 22q11.2 и 10p13-14 не показано у всех пациентов с врожденным пороком сердца. Кроме того, конотрункальные болезни сердца имеют многофакторную основу, такую как генетическое родство и рецессивные мутации некоторых генов, вовлеченных в кардиальный морфогенез. Проводится генетическое исследование роли близкородственных браков и некоторых генов, связанных с врожденным пороком сердца, в алжирской популяции. Это исследование будет также сфокусировано на профилактической работе в семьях с факторами риска и на важности генетического консультирования перед вступлением в брак.